Magnesium Technology 2013 - Hort, Norbert; Mathaudhu, Suveen; Neelameggham, Neale; Alderman, Martyn (The Minerals, Metals & Materials Series, 2016)
The Magnesium Technology Symposium, the event on which this volume is based, is one of the largest yearly gatherings of magnesium experts in the world. Papers reflect all aspects of the field including primary production to applications, recycling, basic research findings, and industrialization. Readers will find broad coverage of current topics, including alloys and their properties, cast products and processing, wrought products and processing, corrosion and surface finishing, ecology, and more. New and emerging applications in such areas as hydrogen storage are also examined.